Status of prenatal and postnatal visits in western China in the background of the new Chinese health system reform: two cross-sectional surveys. (December 2017) - Fan, Xiaojing; Zhou, Zhongliang; Dang, Shaonong; Xu, Yongjian; Gao, Jianmin; Zhou, Zhiying; Su, Min; Wang, Dan; Chen, Gang
Abstract: Background: WHO recommends that women should receive at least four prenatal visits during pregnancy and at least postnatal visits after delivery. There is limited nationally representative data regarding the status of prenatal and postnatal visits since the latest health-system reform was initiated in 2009 in Shaanxi, China. The purpose of this study was to explore the current status of prenatal and postnatal visits in the background of new health-system reform. Methods: Data were drawn from two rounds of the National Health Service Survey in Shaanxi Province, which were done before and after health-system reforms in 2008 and 2013, respectively. Concentration index was used to measure the degree of income-related inequality in use of maternal health services. We obtained verbal informed consent. The study was approved by the Ethics Committee of Xi'an Jiaotong University Health Science Center (Approval No. 2015–644), and it conformed to the ethics guidelines of the Declaration of Helsinki. Findings: The study sample consisted of 2398 women aged 15–49 years. The data of the 5th National Health Services Survey in 2013 showed that, in the criterion of WHO, the percentage of women receiving at least four prenatal visits were 85% in urban areas and 82% in rural areas. The percentage of women receiving at least three postnatal visits was 26% in urban areas and 25% in rural areas. As for women in urban areas, the concentration index of postnatal visit use was −0·075 (95% CI −0·148 to −0·020) after the health-system reform. Interpretation: This study showed that the use of prenatal and postnatal visits met WHO requirements. The new health-system reform increased the use of postnatal visits for poor women in urban areas. These findings show whether or not the health system reform has improved the maternal health services use. However, all the data were collected by a self-report approach, and there might be recall bias. Funding: National Program for Support of Top-notch Young Professionals and China Medical Board (15-227).